Pemanfaatan Data Warehouse pada Institusi Pemerintahan - Rudy Rudy (Bina Nusantara University, 2012)
Data warehouse has a very important role in assisting of decision making, where the data warehouse became the core. Data in the data warehouse provide valuable information for its users. By using data warehouse, governance institutions can conduct data analyzes in order to build new strategies to make benefits for all stakeholders. This paper discusses about the design of data warehouse in Balai Besar Riset Sosial Ekonomi dan Kelautan. Data warehouse design using dimensional model approach introduced by Kimball. The information required by management at Balai Besar Riset Sosial Ekonimi dan Kelautan are divided into three groups: income, consumption and commerce. With the data warehouse organizations can easily perform analyses and generate reports, which can be viewed from various scopes, including time, region, fishermen and fisheries.